2003
DOI: 10.1242/jcs.00727
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Va and microtubule-based motors are required for fast axonal retrograde transport of tetanus toxin in motor neurons

Abstract: Using a novel assay based on the sorting and transport of a fluorescent fragment of tetanus toxin, we have investigated the cytoskeletal and motor requirements of axonal retrograde transport in living mammalian motor neurons. This essential process ensures the movement of neurotrophins and organelles from the periphery to the cell body and is crucial for neuronal survival. Unlike what is observed in sympathetic neurons, fast retrograde transport in motor neurons requires not only intact microtubules, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 70 publications
4
77
0
6
Order By: Relevance
“…Thus, mutant SOD1 may sequester dynein within these aggregates, reducing the efficiency of dynein-mediated transport. In WT embryonic MNs, inhibition of dynein, which is critical for H C trafficking, reduces the fastest speed component of retrograde transport (30). A similar effect is found in SOD1 G93A mice in vivo (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Thus, mutant SOD1 may sequester dynein within these aggregates, reducing the efficiency of dynein-mediated transport. In WT embryonic MNs, inhibition of dynein, which is critical for H C trafficking, reduces the fastest speed component of retrograde transport (30). A similar effect is found in SOD1 G93A mice in vivo (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…The speed distribution of retrograde carriers in cultured MNs was best described by the sum of speed components identified by Gaussian distributions centered at 0, 0.53, and 0.95 μm/s (details in Materials and Methods) (30). As expected by their speed distribution curve (Fig.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, either EHNA or vanadate, which both inhibit dynein and other enzymes, inhibits axonal transport (Ekstrom and Kanje, 1984;Wang et al, 1995;Lalli et al, 2003). More specific dynein inhibition by genetic mutation causes changes in axonal organelle distributions consistent with transport defects (Bowman et al, 1999;Martin et al, 1999a;Koushika et al, 2004).…”
Section: Motors For Axonal Transport Of Mitochondriamentioning
confidence: 99%
“…A number of studies have shown roles of MYO5 in neuronal transportation, exocytosis and synaptic plasticity 19 . For example, MYO5A transports endoplasmic reticulum vesicles 20 , secretory vesicles 21 , tetanus toxin 22 or mitochondria 23 in axons and mRNA/protein complex into dendritic spines 24 . Moreover, MYO5 controls exocytosis of large dense core vesicles 25 and the recycling of AMPA-type glutamate receptors to dendritic spines [26][27][28] .…”
mentioning
confidence: 99%